Human resource management international perspectives - Schuler, Randall S. (Thomson South-Western, 2006)
Includes organizing themes such as strategy, teams, diversity, global issues, and change. This book emphasizes the HR Triad (employee, line manager, HR manager) with the understanding that effective human resource management requires mutual understanding and collaboration among HR professionals, managers, and all other employees